Success in increasing physical activity (PA) among patients with type 2 diabetes: a self-determination theory perspective - Anne M. Koponen; Nina Simonsen; Sakari Suominen (Health Psychology and Behavioral Medicine, 2018)
Background Increased physical activity (PA) is crucial for achieving and maintaining glycemic control and is beneficial for overall well-being of patients with type 2 diabetes as well. Despite that, many patients fail to make changes in their exercise behavior. Self-determination theory (SDT) addresses this problem and suggests that perceived autonomy support, autonomous motivation and self-care competence play a key role in the process of health behavior change. This study investigated the impact of these three factors on success in increasing PA among patients with type 2 diabetes but considered also the role of other important life-context factors, such as mental health, stress and social support. The effect of these other factors may outweigh the effect of SDT constructs; however, previous studies based on SDT have largely overlooked them. Methods This cross-sectional mail survey was carried out in 2011. Out of 2866 respondents, those who had been over 2 years in care in their present and principal primary care health center and had during the past two years tried to increase PA either with or without success (n = 1256, mean age 63 years, 52% men), were included in this study. Logistic regression and mediation analyses were the main methods used in the data analysis. Results Autonomous motivation predicted success in increasing PA even after controlling for the effect of other important life-context factors. Other predictors of success were felt energy, good perceived health, younger age and less social support. Autonomous motivation mediated the effect of perceived autonomy support from a doctor on success in increasing PA. Conclusion The results were in line with SDT showing the importance of autonomous motivation for success in increasing PA. Doctor–patient relationships and lifestyle interventions should focus on promoting self-motivated reasons for health behavior change.